Purification and biochemical characterization of IMP-13 metallo-β-lactamase - Santella, Gisela (2011)
The IMP-13 metallo-β-lactamase was overproduced in Escherichia coli BL21(DE3) and purified by chromatography. Analysis of kinetic parameters revealed some notable differences with other IMP-type enzymes, noteworthily a higher catalytic efficiency toward ticarcillin and piperacillin and a marked preference for imipenem over meropenem.